Myeloproliferative Neoplasms in Children and Adolescents and Thrombosis at Unusual Sites: The Role of Driver Mutations. Issue 6 (August 2019) - Tafesh, Laith; Musgrave, Kathryn; Roberts, Wing; Plews, Dianne; Carey, Peter; Biss, Tina
Abstract : Myeloproliferative neoplasms (MPNs) in childhood and adolescence are rare and seldom complicated by thrombosis. We describe 3 cases of thrombosis at unusual sites in young patients with MPNs. In the pediatric MPN population, unlike in adult MPNs, a clonal mutation is identifiable in only a minority of cases (22% to 26%). All 3 of these individuals had JAK2 mutations driving the disease process. A literature search identified 19 cases of MPN-associated thrombosis in children. Seventeen of the 19 children (89.5%) had a driver mutation. These cases suggest that identifiable driver mutations may confer an increased thrombotic risk in children with MPNs.